On a Problem Of Maximization of Some Indicators in the Discrete Time Models of Economic Dynamics - Sabir Isa Hamidov (International Journal of Mathematics And its Applications, 2017)
We consider $n$ single-product models, each of which is given by the production function and the safety coefficient. The total workforce is also given which is distributed between these models in such a way that to maximize the total consumption, total production and total national wealth. As the production functions of the models is considered the Cobb-Douglas function with constant elasticity substitution (CES). The conditions are given under which the total consumption, total production and total national wealth reaches maximum.